Sustainable construction in the real estate value chain through land conversion planning and development activities: a study in the greater Durban area - Young, Dean (Department of Construction Economics and Management, 2021)
Construction activities have a significantimpact on the community, the economy and the environment and thus a holistic and sustainable approach is required to address the negative impacts. Sustainability is assessed in terms of the triple bottom line, environmental, social, and economic elements. It is argued that the master developer and government agencies set the scene for sustainable construction in the real estate value chain. This research aims to establish the barriers to sustainable construction and the strategies necessary to overcome the barriers to sustainable construction in the real estate value chain from an agricultural land conversion to urban use perspective. A mixed method study was undertaken to examine the knowledge and understanding of agricultural land conversion real estate developers and professionals, as well as end-users, in adopting sustainable construction in real estate development within the context of Durban, South Africa real estate business environment and examines the gap and barriers between knowledge and implementation. A mixed methodology was applied in this study, comprising of 27 questionnaires and 9 interviews with experts in the field of land conversion activities. The sample size was limited, due to the limited number of firms involved in land conversion activities in Durban and was further limited by the number of senior decision makers that responded to the surveys and interviews. The findings highlighted that, due to the limited awareness and training, limited incentives and subsidies and the perceived higher cost of sustainable construction, strategies should be employed to improve the implementation of sustainable construction throughout the real estate value chain at a precinct level.